Strategi Pimpinan dalam Meningkatkan Efektivitas Pembelajaran Tilawatil Qur’an di Rumah Qur’an Umi Kartini Medan - Rahmad Safii; Hasnun Jauhari Ritonga (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research discusses the Umi Kartini Qur'an House in increasing effectiveness Learning Tilawatil Qur'an for Children in Indrakasih Village, Medan Tembung District Medan City, with the topic of leadership strategies for improving effectiveness of learning at the Umi Kartini Qur'an House in increasing interest in learning reading the Koran to children in Indrakasih Village, Medan City and the implications of the Qur'an House Umi Kartini in increasing interest in learning to read the Koran among children in the village Indrakasih Medan City. The method used in this research is a qualitative method and is descriptive-analytical in nature. Jacob (Marshall, 1999) describes six types of qualitative methods, namely Human Ethology (human ethology), Holistic Ethnography, Cognitive Anthropology, Ethnography Communication, Symbolic Interaction (Symbolic Interaction), Environmental Psychology (Ecology Psychology). The aim of the research. First, want to know the strategy the head of the Umi Kartini Qur'an House in increasing interest in learning to read the Koran in children in Indrakasih Village, Medan City. Second, I want to know the implications of the Qur'an House Umi Kartini in increasing interest in learning to read the Koran among children in the village Indrakasih Medan City.